Grey Matters A Guide for Collaborative Research with Seniors - Emes, Claudia; Marlett, Nancy (University of Calgary Press, 2010)
This study marks a major step in making collaboration between seniors, academic researchers, and community researchers a reality. Many aging adults are motivated to undertake research projects in later life or even return to university after retirement. Grey Matters is the result of a pilot project developed to study the effectiveness of collaborative research involving seniors. Because the project was such a success, the authors were encouraged to make their model available both to seniors interested in undertaking their own research and to those hoping to involve seniors in collaborative research. This guide provides a helpful framework for making the most of research projects by and with seniors, including sections on such techniques as narrative interviews, focus groups, and surveys. Grey Matters will be the first Open Access book published by the University of Calgary Press. On October 22, 2010, it will be released simultaneously in traditional print book format and as a free downloadable PDF file from this website.